Cargo crime within Malaysia logistics industry / Nur Zulaikha Samsudin - Samsudin, Nur Zulaikha (2014)
Recently, cargo crime has become a divisive issue and critically discussed in the year 2001 after the September 11 attack Cargo crime includes hijacking, warehouse theft, lost in transit and many more. In Malaysia, the study regarding cargo crime was yet to be found in any research and very limited articles in Malaysia that discuss on this issue. The purpose of this research had carried out is to study on the cargo crime scenario specifically within logistics industry in Malaysia. The study is focusing on the cargo crime on the road that was normally involved hijacking of hauliers and lost in transit incidents. The issues of concern in the cargo crime that supporting this research includes lost in transit that keep on increasing each year, the increase of high value of the shipment stolen, and the insecure technology leads to the lost shipment. The steps of methodology involved in this research are qualitative study and hypothesis testing. Exploratory study is included under qualitative study, where it involves the interview methods, while hypothesis testing is to explain the relationships and to differentiate two or more factors in the research using questionnaires and analysis. The overall findings in this thesis showed that there were three main factors that influence to the increase in cargo crime, which include; (1) desirable goods, (2) lack of transport security, and (3) lack of security procedure. From the overall findings this research had found that the cargo crime issues did related to the unawareness of the logistics company towards security. This is due to most of the logistics company did not have a proper security procedure and a proper installation of security system in their vehicle. The overall findings had highly recommended that all logistics companies should tighten their security plans such as establish a proper security procedure, to join the logistics association, and to report all cases regarding cargo crime to the police as it may warn the other logistics company regarding cargo crime The implication of this research towards the industrial players, government and education is to provide the information regarding the actual scenario of cargo crime and the seriousness level of cargo crime in Malaysia. This is research also has become the first study of cargo crime on the road in Malaysia that describe and analyze the actual scenario regarding cargo crime on the road focusing on Malaysia logistics industry. From the research, it can be concluded that the information in this research may increased the level of awareness of cargo crime.